2016
DOI: 10.1093/nar/gkw1059
|View full text |Cite|
|
Sign up to set email alerts
|

Not5-dependent co-translational assembly of Ada2 and Spt20 is essential for functional integrity of SAGA

Abstract: Acetylation of histones regulates gene expression in eukaryotes. In the yeast Saccharomyces cerevisiae it depends mainly upon the ADA and SAGA histone acetyltransferase complexes for which Gcn5 is the catalytic subunit. Previous screens have determined that global acetylation is reduced in cells lacking subunits of the Ccr4–Not complex, a global regulator of eukaryotic gene expression. In this study we have characterized the functional connection between the Ccr4–Not complex and SAGA. We show that SAGA mRNAs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
0
43
1
Order By: Relevance
“…Recent work revealed widespread cotranslational assembly of protein complexes (Shiber et al, 2018), including S. cerevisiae SAGA (Kassem et al, 2017). In marked contrast, we did not observe evidence for cotranslational assembly of Tra1 and Tra2 into SAGA and NuA4, respectively.…”
Section: Cotranslation Interaction Between the Ttt Cochaperone And Itcontrasting
confidence: 99%
See 1 more Smart Citation
“…Recent work revealed widespread cotranslational assembly of protein complexes (Shiber et al, 2018), including S. cerevisiae SAGA (Kassem et al, 2017). In marked contrast, we did not observe evidence for cotranslational assembly of Tra1 and Tra2 into SAGA and NuA4, respectively.…”
Section: Cotranslation Interaction Between the Ttt Cochaperone And Itcontrasting
confidence: 99%
“…Cotranslational assembly has emerged as a prominent regulatory mechanism for promoting protein-protein interactions and the building of a complex (Duncan and Mata, 2011;Shiber et al, 2018;Shieh et al, 2015). Specifically, cotranslational interactions were observed for the SET1C histone methyltransferase complex (Halbach et al, 2009) and, more recently, between specific SAGA subunits (Kamenova et al, 2018;Kassem et al, 2017). Finally, a recent study demonstrated that Taf5, which is shared between SAGA and the general transcription factor TFIID, require a dedicated chaperone, the CCT chaperonin, for incorporation into pre-assembly modules (Antonova et al, 2018).…”
Section: Chaperone-mediated Cotranslational Folding Of Tra1 and Tra2 mentioning
confidence: 99%
“…Cotranslational association is favored in those cases where subunits are especially aggregation-prone [26]. Also yeast protein complexes, such as histone-modifying complexes methyl-transferase (SET1C) [115] and acetyltransferase (SAGA) assemble cotranslationally [116], as do cyclin protein complexes [117]. The ribosome may modulate the assembly of protein complexes by stabilizing individual protein domains or subunits [100] or adjusting the speed of translation [47] downstream of interaction domain boundaries [30].…”
Section: Cotranslational Subunits Assemblymentioning
confidence: 99%
“…Transporting a single mRNA is energetically efficient because a single mRNA molecule can be used to synthesize multiple copies of proteins, 43 reviewed more extensively here 2, 18, 44 . Similarly, colocalization of mRNAs encoding members of a protein complex could produce high concentrations of multisubunit complex components in a specific location, thus increasing complex formation efficiency and decreasing the formation of off‐target, nonfunctional complexes 45–48 . mRNAs can also be localized in a translationally silenced form.…”
Section: How Does Rna Get There?mentioning
confidence: 99%
“…Localization of these seven separate transcripts to protrusions aid in Arp2/3 assembly through local translation and assembly. In some cases, local translation of protein complex members can result in cotranslational assembly as observed for heteromeric ion channels 47 and histone acetyltransferase 48 …”
Section: How Does Rna Get There?mentioning
confidence: 99%